Tuberculosis screening in asylum seekers in Germany, 2015: characteristics of cases and yield. Issue 4 (26th October 2017) - Fiebig, Lena; Hauer, Barbara; Andrés, Marta; Haas, Walter
In 2015, according to the International Organization for Migration (IOM), 244 million people worldwide were international migrants, representing the highest number ever recorded [1]. The level of forced displacement globally was the highest since World War II, with a dramatic increase in the number of refugees, asylum seekers and internally displaced people. Germany became one of the largest recipients of first asylum seeking claims [2]. TB screening among asylum seekers in Germany identified 1255 cases in 2015, and may have decreased TB exposure http://ow.ly/2d4n30f9w9b